Sensus Communis: Some Perspectives on the Origins of Non-synchronous Cross-Sensory Associations - Guellaï, Bahia; Callin, Annabel; Bevilacqua, Frédéric; Schwarz, Diemo; Pitti, Alexandre; Boucenna, Sofiane; Gratier, Maya (Frontiers in Psychology, 2019)
Adults readily make associations between stimuli perceived consecutively through different sense modalities, such as shapes and sounds. Researchers have only recently begun to investigate such correspondences in infants but only a handful of studies have focused on infants less than a year old. Are infants able to make cross-sensory correspondences from birth? Do certain correspondences require extensive real-world experience? Some studies have shown that newborns are able to match stimuli perceived in different sense modalities. Yet, the origins and mechanisms underlying these abilities are unclear. The present paper explores these questions and reviews some hypotheses on the emergence and early development of cross-sensory associations and their possible links with language development. Indeed, if infants can perceive cross-sensory correspondences between events that share certain features but are not strictly contingent or co-located, one may posit that they are using a ‘sixth sense’ in Aristotle’s sense of the term. And a likely candidate for explaining this mechanism, as Aristotle suggested, is movement.